Artificial Intelligence for Surveillance in Public Health - Thiébaut, Rodolphe; Cossin, Sébastien; Section Editors for the IMIA Yearbook Section on Public Health and Epidemiology Informatics (Yearbook of Medical Informatics, 2019)
Objectives: To introduce and summarize current research in the field of Public Health and Epidemiology Informatics.Methods: The 2018 literature concerning public health and epidemiology informatics was searched in PubMed and Web of Science, and the returned references were reviewed by the two section editors to select 15 candidate best papers. These papers were then peer-reviewed by external reviewers to give the editorial team an enlightened selection of the best papers.Results: Among the 805 references retrieved from PubMed and Web of Science, three were finally selected as best papers. All three papers are about surveillance using digital tools. One study is about the surveillance of flu, another about emerging animal infectious diseases and the last one is about foodborne illness. The sources of information are Google news, Twitter, and Yelp restaurant reviews. Machine learning approaches are most often used to detect signals.Conclusions: Surveillance is a central topic in public health informatics with the growing use of machine learning approaches in regards of the size and complexity of data. The evaluation of the approaches developed remains a serious challenge.
Keywords: Public health; epidemiology; surveillance; medical informatics; International Medical Informatics Association; artificial intelligence